A hidden Rodinian lithospheric keel beneath Zealandia, Earth's newly recognized continent - Turnbull, Rose E.; Schwartz, J.J.; Fiorentini, M.L.; Jongens, R.; Evans, N.J.; Ludwig, Thomas; McDonald, B.J.; Klepeis, K.A. (Geology, 2021)
We present a data set of >1500 in situ O-Hf-U-Pb zircon isotope analyses that document the existence of a concealed Rodinian lithospheric keel beneath continental Zealandia. The new data reveal the presence of a distinct isotopic domain of Paleozoic-Mesozoic plutonic rocks that contain zircon characterized by anomalously low δ18O values (median = +4.1‰) and radiogenic εHf(t) (median = +6.1). The scale (>10,000 km2) and time span (>>250 m.y.) over which plutonic rocks with this anomalously low-δ18O signature were emplaced appear unique in a global context, especially for magmas generated and emplaced along a continental margin. Calculated crustal-residence ages (depleted mantle model, TDM) for this low-δ18O isotope domain range from 1300 to 500 Ma and are interpreted to represent melting of a Precambrian lithospheric keel that was formed and subsequently hydrothermally altered during Rodinian assembly and rifting. Recognition of a concealed Precambrian lithosphere beneath Zealandia and the uniqueness of the pervasive low-δ18O isotope domain link Zealandia to South China, providing a novel test of specific hypotheses of continental block arrangements within Rodinia.